Discovery Character Experiment Worksheet on Temperature and Heat Material of Grade X Vocational School - Lieza Fadzilah; Tantri Mayasari; Andista Candra Yusro (Universitas Pendidikan Ganesha, 2020)
Student Worksheet (LKS) is a learning media for experimental activities which as a source of student learning which can provide experiences for students, develop skills, and influence their attitudes. The purpose of this study is to produce a Worksheet Discovery-Character Experiment to hone the scientific attitudes and character of students that are suitable to be used in learning. This research is a 4D development study but only reached the development stage. Data collected in the form of LKS feasibility data from experts (lecturers and teachers). Based on the results of the analysis, it was concluded that the Discovery-Character Experiment worksheet (discovery learning integrated character education) is very feasible to use with an average percentage of 93%. This worksheet is equipped with 3 Temperature and Heat experiment worksheets, concept maps, discussion material, practice questions, and self-evaluation related to students' scientific attitudes and characters. Based on the results of the study, it was concluded that the worksheet was arranged using discovery learning that is integrated in character education at the temperature and heat material of class X vocational high school. Each learning activity which integrated discovery learning can build students’ character and scientific attitude.